Atmospheric heat sinks over the western Tibetan Plateau associated with snow depth in late spring. (23rd May 2019) - Xiao, Zhixiang; Duan, Anmin; Wang, Ziqian
Abstract: The atmospheric heat source/sink (AHS) and snow cover/depth over the Tibetan Plateau (TP) in late spring play important roles in modulating the evolution of Asian summer monsoons. However, quantitative estimation of the AHS over the TP is still a large challenge because of limited observational data. In this work, both data analyses and numerical simulations from the Weather Research and Forecasting model with an updated daily snow‐depth data set are conducted to explore the intrinsic connection between the AHS and snow depth over the TP in May. Data analyses indicate that only a weak negative relationship exists between snow depth and the AHS over the western TP. On the other hand, despite the overall consistency in the spatial pattern of the AHS between the reanalysis data sets and the Weather Research and Forecasting model, a strong cooling effect (about −14.4 W/m 2 ) appears over the western TP (32°–40°N, 70°–78°E) and the Nyenchen Tanglha Mountains in the simulation, where the altitude is above 4, 000 m with thick snow cover. This characteristic is opposite to that observed in reanalysis data sets. Further analysis indicates that the underestimated atmospheric net longwave radiative cooling effect that is associated with snow depth may exaggerate the atmospheric heat source in current reanalysis data sets. Large uncertainties in the AHS still exist in current state‐of‐the‐art reanalysis data sets, especially over the regions of the TP covered by snow. Abstract : Climatological distributions of snow depth (units: cm) over the TP in (a) May, (b) June, (c) July, and (d) August. Black solid lines and dashed curved lines outline the areas of the TP with an average altitude greater than 2000 and 4, 000 m, respectively. The red rectangle in (a) represents the area (32°–40°N, 70°–78°E), covered by thick snow, over the western TP. That rectangle has the same meaning in the following figures